Senhoras de engenhos na primeira metade do século XIX - Silva, Jane Cleide dos Santos (2022)
Over the last decades, it has been perceived the need to expand studies on gender relations that embrace issues of sexuality, daily life, social movements, mentalities, profession, religion, ethnicity, etc. Thus, the growing and relevant increase in academic productions with quality research has contributed to a vital scientific look at the subject of women and formed a broad thematic and diverse field of works about women's life and condition. For this, it was fundamental to uncover the role of women in the various fields in which they have always been present, to create a new vision that reveals the thought and presence of women in the past, that rescues them from silencing, from the position of inferiority, so that it is possible to identify their participation in the arduous construction and contribution in the past, be it in the social, economic, and political fields, even though in a macho, patriarchal, and stratified society that for a long time undervalued women's work and performance, especially in those jobs considered "men's work". In the patriarchal and aristocratic environment, women were important elements of the strategy for maintaining the property, increasing the patrimony and the continuity of the lineage through marriage. With this purpose, we turned our attention to the performance of women in the first half of the 19th century in Brazil, especially in the Northeast region, with emphasis on the work of women in sugar estates in Sergipe Del Rey, in order to rediscover the position and performance of women who lived in the world of the mills, from aristocratic families and social prestige, heirs and owners of sugar cane units so important to the local economy. To know women owners of sugar mills and sugar cane farms in Sergipe and how they acted in the administration of their businesses, properties and family.